Radiotherapy with rituximab may be better than radiotherapy alone in first-line treatment of early-stage follicular lymphoma: is it time to change the standard strategy - Janíková, Andrea; Bortlíček, Zbyněk; Campr, Vít; Kopálová, Nataša; Benešová, Kateřina; Belada, David; Procházka, Vít; Pytlík, Robert; Vokurka, Samuel; Pirnos, Jan; Duras, Juraj; Móciková, Heidi; et al. (Leukemia & lymphoma, 2015)
Early-stage follicular lymphoma (FL) has traditionally been treated with involved-field radiotherapy (RT). Rituximab (R) is a low-toxic, efficient systemic therapy for FL, but there are no data about its clinical impact in early FL. We retrospectively analyzed 93 patients with stage I-II indolent FL treated with RT (n=65) or RT+R (n=14) or R alone (n=14). Median follow-up was 5.0 years for patients with RT, 2.8 years for the RT+R subgroup and 2.5 years for patients treated with R. The complete response rate was 92%, 100% and 86% (not significant) and the median PFS was 3.3 years, not reached and 4.9 years (p=0.035) for the RT, RT+R and R arms, with no impact on overall survival. R combined with RT seems to give better results in terms of global FL control, but longer follow-up and prospective comparison are needed to verify these results.
Keywords: senioři; Lymphoma, Follicular; Male; Female; kombinovaná terapie; Aged; Middle Aged; Treatment Outcome; rituximab; protinádorové látky; folikulární lymfom; Česká republika; Neoplasm Staging; Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Radiotherapy; mužské pohlaví; mortalita; ženské pohlaví; staging nádorů; Adult; Czech Republic; Databases, Factual; senioři nad 80 let; Rituximab; dospělí; Standard of Care; lidé středního věku; Mortality; výsledek terapie; databáze faktografické; Aged, 80 and over; Chemoradiotherapy; protokoly protinádorové kombinované chemoterapie; lidé; radioterapie; Humans; standardní péče; Combined Modality Therapy; chemoradioterapie